The Practice of Underage Marriage in Bathin VIII District Positive Legal Perspectives and Islamic Law - M. Mizan Azrorizain; Hermanto Harun; Husin Bafadhal (Dinasti International Journal of Management Science, 2022)
This study aims to reveal the problem of underage marriage and how according to positive law and Islamic law on this matter, with sub-focuses including: (1) Explanation of the practice of underage marriage in Bathin VIII District, Sarolangun Regency. (2) An explanation of the causes of the practice of underage marriage in Bathin VIII District, Sarolangun Regency. (3) An explanation of the perspective of positive law and Islamic law on underage marriage in Bathin VIII District, Sarolangun Regency. This study uses a descriptive qualitative research method with a variety of casuistic research. Data was collected by using in-depth interviews, observation, and documentation techniques. The data analysis technique uses interactive analysis with a cyclical interactive model. The results showed that there were three findings. First, underage marriages that occurred in Bathin VIII District, Sarolangun Regency. is a tradition that often occurs among the majority of people, so that underage marriages often occur because they think that as long as the marriage is religiously valid and the family's parents also agree, the marriage can be carried out by ignoring several things related to marriage , including the physical and psychological children and also laws. Second, the factors for the occurrence of underage marriages are low education, economic factors, and being influenced by the surrounding environment, keeping children from things that are not wanted, people have already been proposed to so "pamali" if rejected and feared that it will be difficult to get a mate afterwards, emergency forced by parents and community traditions, and coercion on the part of parents and family than he does something that he does not want, it is better for him to get married. Third, the positive legal perspective of Indonesia through Law Number 16 of 2019 concerning Marriage has determined the minimum age for marriage to be allowed, namely 19 years for women and 19 years for men. If the prospective bride and groom have not reached the minimum age, the relevant parties must arrange marriage dispensation at the local Religious Court. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age for marriage so that the prospective bride and groom reach maturity of body and soul, in order to realize the goal of a good marriage. and coercion on the part of parents and family than he does something that he does not want, it is better for him to get married. Third, the positive legal perspective of Indonesia through Law Number 16 of 2019 concerning Marriage has determined the minimum age for marriage to be allowed, namely 19 years for women and 19 years for men. If the prospective bride and groom have not reached the minimum age, the relevant parties must arrange marriage dispensation at the local Religious Court. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age for marriage so that the prospective bride and groom reach maturity of body and soul, in order to realize the goal of a good marriage. and coercion on the part of parents and family than he does something that he does not want, it is better for him to get married. Third, the positive legal perspective of Indonesia through Law Number 16 of 2019 concerning Marriage has determined the minimum age for marriage to be allowed, namely 19 years for women and 19 years for men. If the prospective bride and groom have not reached the minimum age, the relevant parties must arrange marriage dispensation at the local Religious Court. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age for marriage so that the prospective bride and groom reach maturity of body and soul, in order to realize the goal of a good marriage. the positive legal perspective of Indonesia through Law Number 16 of 2019 concerning Marriage has determined the minimum age for marriage to be allowed, namely 19 years for women and 19 years for men. If the prospective bride and groom have not reached the minimum age, the relevant parties must arrange marriage dispensation at the local Religious Court. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age for marriage so that the prospective bride and groom reach maturity of body and soul, in order to realize the goal of a good marriage. the positive legal perspective of Indonesia through Law Number 16 of 2019 concerning Marriage has determined the minimum age for marriage to be allowed, namely 19 years for women and 19 years for men. If the prospective bride and groom have not reached the minimum age, the relevant parties must arrange marriage dispensation at the local Religious Court. Islamic law through the Compilation of Islamic Law (KHI) has determined the minimum age for marriage so that the prospective bride and groom reach maturity of body and soul, in order to realize the goal of a good marriage.